Philosophical Analysis of Elements of Human Power System - Holmirzaev Hurshid Naqibillaevich (Peerian Journals Publishing, 2022)
The article scientifically examines the structure of human potential. The category of human capital has been shown as one of the directions of human potential theory
Keywords: human potential; human capital; Social capital; political capital